Pengaruh Kecerdasan Emosional Terhadap Komitmen Organisasi Melalui Kepuasan Kerja Sebagai Variabel Mediasi pada Bank DKI Kantor Cabang Surabaya - Riza Mutimma Auda (BISMA (Bisnis dan Manajemen), 2018)
DKI Bank is a commercial bank and Regional Enterprises which is owned by Jakarta Provincial Government and PD Pasar Jaya. DKI Bank now has grown into a commercial bank that has IDR 30.74 trillion assets, with the office network reached 221 offices in Jakarta and other major cities in Indonesia, and 2,549 human resources employee and range of banking products and services to more than one million customers.This rapid development occurs because of their employees who properly implement the organization's commitment to the company for the betterment of the company. Organizational commitment cannot be separated from emotional intelligence employee and satisfaction work which is obtained by employees. This study aims to identify and explain the influence of emotional intelligence toward organizational commitment through job satisfaction as a mediating variable. This is causal research using quantitative approach. The sampling technique using 72 respondents saturated sample and collected as many as 64 respondents in DKI Bank Branch Office Surabaya. The statistical analysis used is Structural Equation Modeling (SEM) with the support of smartPLS software.This study results explains that emotional intelligence has positive and significant effect on job satisfaction. Job satisfaction has positive effect and significant on organizational commitment. Emotional intelligence has positive and significant effect on organizational commitment. Job satisfaction mediates the influence of emotional intelligence on organizational commitment.